2016
DOI: 10.3389/fpsyg.2016.01803
|View full text |Cite
|
Sign up to set email alerts
|

Training Early Literacy Related Skills: To Which Degree Does a Musical Training Contribute to Phonological Awareness Development?

Abstract: Well-developed phonological awareness skills are a core prerequisite for early literacy development. Although effective phonological awareness training programs exist, children at risk often do not reach similar levels of phonological awareness after the intervention as children with normally developed skills. Based on theoretical considerations and first promising results the present study explores effects of an early musical training in combination with a conventional phonological training in children with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 40 publications
(74 reference statements)
0
13
0
3
Order By: Relevance
“…For future research concerning the promotion of literacy skills and literacy-related skills, a consecutive training regime combining musical training (helping to enhance the processing of temporal and spectral auditory cues in speech and thus supporting the development of phoneme perception and phonological processing) with training in phonological awareness might be an especially fruitful approach. However, a recent training study by Kempert et al (2016) did not find incremental training effects on phonological awareness in an intervention group receiving music training prior to a phonological awareness intervention in comparison to a second intervention group receiving a training of phonological awareness only. This lack of effects might be attributable to low training intensity as well as the fact that a broad range of music facets was trained (Kempert et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For future research concerning the promotion of literacy skills and literacy-related skills, a consecutive training regime combining musical training (helping to enhance the processing of temporal and spectral auditory cues in speech and thus supporting the development of phoneme perception and phonological processing) with training in phonological awareness might be an especially fruitful approach. However, a recent training study by Kempert et al (2016) did not find incremental training effects on phonological awareness in an intervention group receiving music training prior to a phonological awareness intervention in comparison to a second intervention group receiving a training of phonological awareness only. This lack of effects might be attributable to low training intensity as well as the fact that a broad range of music facets was trained (Kempert et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
“…However, a recent training study by Kempert et al (2016) did not find incremental training effects on phonological awareness in an intervention group receiving music training prior to a phonological awareness intervention in comparison to a second intervention group receiving a training of phonological awareness only. This lack of effects might be attributable to low training intensity as well as the fact that a broad range of music facets was trained (Kempert et al, 2016). Concentrating on the training of specific music processing skills such as rhythm processing or other temporal musical skills might be more promising (see, e.g., Overy, 2003; Moritz et al, 2013; Hallam, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…In fact, music training has failed to offer any specific advantage in terms of both cognitive enhancement and academic achievement. These conclusions are made even stronger if we take into consideration that music training has been found substantially ineffective even at enhancing those skills traditionally believed to be tightly close to music skill, such as phonological processing and literacy (e.g., Kempert et al, 2016).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 96%
“…However, Kempert et al (2016) studied German children and found that speech training had a significant impact on phonological awareness, while music training had no significant effect on phonological awareness.…”
Section: Music Training and Phonological Awarenessmentioning
confidence: 99%